ENTREPRENEURSHIP SISWA SMK - -, Sudirman; Sari, Dian Cita (PRODU-Prokurasi Edukasi (Jurnal Manajemen Pendidikan Islam), 2019)
This study aims to determine: (1) obtain a descriptive understanding of students' entrepreneurship, family environment, school environment, and peer interaction among vocational students, (2) knowing the influence of personality, family environment, school environment, and peer interaction both together and individually in the entrepreneurship of vocational students, and (3) knowing how much influence the personality factors, family environment, school environment, and interactions peers together towards entrepreneurship in vocational students. This research is a survey research with ex post facto approach. Data analysis techniques used were descriptive analysis, simple linear regression analysis and multiple regression analysis using of SPSS 20 software. The results showed that: (1) high entrepreneurship (50.5%), high personality (73.3%), high family environment (49.5%), high school environment (69.5%) and high peer interactions (44.8%), (2) there is an influence of personality, family environment, school environment, and peer interaction individually or together to entrepreneurship, and (3) effective contribution of personality variables, family environment, school environment, and peer interaction together towards entrepreneurship by 68.6% and the effective contribution of each variable namely family environment 53.5%, personality 9.7%, peer interaction 3.9%, and school environment 1.6 %.